A Preliminary Investigation on Soils in Relation to the Occurrence of Spike in Sandal (Santalum album) - Khan, M. A. Waheed; Yadav, J. S. P. (Indian Forester, 1962)
Owing to the rapid spread and immense loss of State revenue, the spike disease of sandal has received considerable attention in recent years. The various conflicting views of the different workers about the cause of this disease and the remedial measures adopted 80 far to control it have been summarised in brief. Inspite of much work done on the subject the problem still remains baffling in the country. It has been shown that our present knowledge of soils in relation to the occurrence of this disease is extremely meagre. An investigation was, therefore, undertaken in Salem North division of Madras State to examine the soils having a bearing on this problem. The analytical data of 16 soil profiles representing both healthy and spiked sandal trees have been reported and discussed in detail. In general, the soils are coarse in texture, neutral in reaction and somewhat low in the nutrient status. A critical comparison of the data showing the two types of health condition, however, reveal a positive correlation of the soil properties with the incidence of the malady. Majority of the soils under spiked condition are calcareous and contain lower quantities of available nutrients especially phosphorus, whereas those carrying healthy growth are all non-calcareous and have relatively higher nutrient availability. The results obtained suggest a wide scope for future research to draw conclusions of greater practical value.